Between two Cultures: About the Ambiguity of the Identities of Descendants of Chinese Immigrants in Spain - Jin, Yangmin; Gómez-Pellón, Eloy (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
This article examines the identity problem of descendants of Chinese immigrants as an effect of the migration. This research was carried out with the Chinese immigrants’ descendants and its fieldwork was obtained in Spain and China. The research aims to analyze how the Chinese immigrants’ descendants construct their ambiguous identities and investigate the factors which they perceive as influencing, such as family, language, prejudices, stereotypes, discriminatory experiences, and so on, that stress and cause the contradictory feelings about their identities. It is concluded that Chinese immigrants’ descendants experience a complicated process of identity construction, which entails ambivalences, confusions, and uncertainties due to some internal and external factors. However, over time, these young people will have the possibility to construct flexible and dialectical identities, which are main and complementary at the same time.
Keywords: Descendants of Chinese immigrants in Spain; the second Chinese generation in Spain; ambiguous identities; conflicting identities; construction of Chinese migrants’ identity in Spain